DEVELOPING CRITICAL READING SKILLS THROUGH IELTS-ORIENTED TASKS IN UNIVERSITY EFL CLASSES - Inoyatova Umida Boxadir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines how IELTS-oriented reading tasks can support the development of critical reading skills among university EFL learners. With the increasing demand for academic literacy in higher education, students must engage with texts beyond literal comprehension to evaluate arguments, infer meaning, and integrate information effectively. Current pedagogical research highlights the potential of exam-oriented tasks as tools for fostering higher-order thinking when combined with strategic instruction. Drawing on recent studies, this article explores theoretical perspectives on task-based reading, cognitive and metacognitive strategies, and the role of reflective practice in enhancing critical reading.